The Analysis of the Concept of Gender in the Drama “Drought and Lie” through the Discourse-Historical Approach of Ruth Wodak - Halimeh Enayat; Marzieh Askari (زن در فرهنگ و هنر)
Art is a fundamental component of the culture of a society, and its motifs can serve as a reflection of the society’s cultural, social, political, and economic status. In this investigation, the text of Mohammad Yaghoubi’s drama “Drought and Lie” from the 2000s serves as the data for analysis. The purpose of this research is to study the concept of gender in the aforementioned text in order to identify the manner in which this concept is generated or perpetuated within the context of the social conditions of Iran in the 2000s. Ruth Wodak’s discourse-historical approach has been selected in the research methodology section. The research results indicate that the drama “Drought and Lie” presents the definition of gender and gender roles in a state that is between the traditional official dominant discourse and the modern discourse (as the rival discourse), which was established in the 2000s, by employing the historical-social horizons of the era and utilizing Wodak’s fivefold strategies to analyze the linguistic aspects of words, phrases, and key contents of the text. The final conclusion posits that the author of the drama “Drought and Lie” has effectively conveyed the position of Iran's transitional society toward modernity in the 2000s, as well as the repercussions of cultural changes in the private sphere of family and marital relations.